A Sharp Decline in Burden of Stroke in Rural China During COVID-19 Pandemic - Liu, Jie; Yang, Qiaoxia; Zhang, Xin; Lin, Qiuxing; Yang, Yuan; Guo, Dandan; Mao, Wenjing; Tu, Jun; Liu, Zeping; Li, Jidong; Ning, Xianjia; Wang, Jinghua (Frontiers in Neurology, 2021)
This study aimed to explore trends in the burden from stroke associated with home quarantine during the COVID-19 pandemic. Patients with a first-ever stroke registered between January 1 and April 20 from 2010 to 2020 were included in this study. We compared the incidence and rates of mortality, hospitalization, and diagnosis by neuroimaging for first-ever stroke among a low-income population in rural China during the study periods. Overall, 377 first-ever stroke patients were analyzed in this study period; men accounted for 59.2%. Compared with 2019, the incidence of first-ever stroke was 73.5% lower in 2020 (P<0.001). The incidence of first-ever stroke was lower by 64.18% in 2020 than in the previous 5 years (P=0.002) and by 65.42% in the previous 10 years (P=0.001). Mortality from first-ever stroke in 2020 was not significantly different from that in 2019, but it was noticeably lower than that for the previous 5 and 10 years. However, rates of hospitalization and diagnosis by neuroimaging remained stable across the study period. These findings suggest that the home quarantine helped reduce outdoor activities at low temperatures, restrict gatherings, reduce alcoholism and high-fat diet, and lower pollution caused by factories, etc. These changes were advantageous for helping high-risk groups to reduce the burden of stroke.